Z GENERATION TOWARDS THE USE OF SMARTPHONE APPLICATION FOR LISTENING ACTIVITIES IN BLENDED-LEARNING - Sari, Valentina Dyah Arum (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2019)
The character of Generation Z which is closely related to the use of technology triggers awareness of educators to facilitate this generation with teaching and learning techniques that are most suitable for them. One of them is by optimalizing the use of gadget or smart phones as learning media for them. Because of this phenomenon, this study was carried out with the aim to find out the use of smartphone application in learning listening acctivities in blended-learning of English general courses followed by first semester students who are included as Z generation. The research also aimed to find out the significance of smartphone application dealing with the improvement of listening skill towards the non-English department students and to figure out the possible obstacles while using the smartphone application. The researcher applied the two selected smartphone applications. In addition to data triangulation, this study also used pre-test and post-test to see the significance. The other instruments were questionnaires and students? listening material summary. The data were analyzed by mixed-method technique, namely qualitative and quantitative. The results show that the students showed a medium positive response to the use of smartphone applications for learning listening skills in blended-learning class and did not encounter obstacles while using the applications. Moreover, the smartphone applications also give high positive affects showed by a significant improvement in results experienced by non-English students in listening skills. keywords: listening skill, smartphone applications, blended-learning